Molecular quantitation and characterization of Vibrio cholerae from different seafood obtained from wetmarket and supermarket - Letchumanan, Vengadesh; Radu, Son; Cheah, Yoke Kqueen (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Vibrio cholerae still represents a significant threat to human health worldwide despite the advances in hygiene, consumer knowledge, food treatment and food processing. In Malaysia, statistics in year 2009 have shown that among the food and water borne diseases, food poisoning has the highest incidence rate of 36.17 per 100,000 populations and with a mortality rate of 0.01 per 100,000 populations. In this study, 22 seafood samples comprising of fish, squid, crustacean and mollusks purchased from wet market and supermarket were analyzed. The Most Probable Number (MPN) and real time PCR was used to enumerate the Vibrio cholerae in seafood sample. The results showed that MPN-real time PCR of the samples from wet market had a maximum of > 1100 MPN/g compare to 93 MPN/g enumerated from the MPN plate. The MPN-real time PCR in the samples from supermarket indicated 290 MPN/g as compared to 240 MPN/g enumerated from the MPN plate. The standard curves showed that there was a good linear correlation between the Ct values. The minimum level of detection of Vibrio cholerae standard DNA at targeted gene was 3 × 10 -5 ng/μl.